Case Report: Robot-assisted sacral fracture reduction with patient-specific finite element planning - Ma, Yupeng; Ge, Junbo; Hong, Huanyu; Huang, Tao; Li, Yu; Sun, Zhengwen; Sun, Tao (Frontiers in Medicine, 2025)
BackgroundSacral fractures are typically caused by high-energy trauma. They often disrupt the pelvic ring and pose complex anatomical challenges, as the sacrum is surrounded by critical structures—including blood vessels, nerves, and internal organs. Traditional open reduction and internal fixation (ORIF) can restore anatomical alignment but requires extensive tissue exposure. This exposure leads to greater tissue trauma, prolonged recovery, and higher risks of infection, hemorrhage, or nerve damage. For these reasons, minimally invasive surgery (MIS) is preferred. However, MIS demands high technical precision. Robot-assisted fracture reduction (RAFR) systems enhance precision in minimally invasive procedures, while finite element analysis (FEA) optimizes preoperative planning by simulating biomechanics. However, clinical evidence for combining these techniques in complex, multi-injury cases is limited.Case presentationA 19-year-old female was admitted to the hospital following high-energy trauma (a fall from height), diagnosed with unstable pelvic fracture (AO C1.3 type), longitudinal sacral fracture (Denis II type with vertical displacement), and multiple concurrent injuries (thoracolumbar fractures, rib fracture, pulmonary contusion, splenic and renal contusions, lumbosacral plexus injury). Preoperative management included supracondylar femoral traction and vital sign stabilization. Preoperative FEA based on the patient’s CT data simulated three internal fixation schemes, showing comparable vertical stability; S1 standard + S2 extended sacroiliac screws were selected to preserve lumbar mobility. The RAFR system was used for surgery: 3D preoperative planning, automatic path design, and intraoperative real-time tracking. Fixation was performed with the selected screws (posterior ring) and an anterior external fixator.ConclusionThis case illustrates the value of combining FEA and RAFR in treating complex sacral fractures with multiple traumas. It highlights that FEA provides a scientific basis for personalized fixation strategy selection, while RAFR achieves precise, minimally invasive reduction, offering a feasible pathway for personalized, minimally invasive management.